A study about the knowledge regarding animal bites and its management among adults in urban Pallavaram (Tamilnadu-India) - V. YASODHA, (International Journal of Pharma and Bio Sciences, 2019)
Animal bite and rabies in india are highly endemic. The country has the highest number of death burden worldwide contributing 36% of the total. Exact case load is unavailable due to inadequate reporting. A community based multi center survey showed the annual incidence to be 2 per 1,00,000 population and the total estimate being more than 20,000 annually. Rabies in animals and humans is still diagnosed on the basis of clinical signs and symptoms in many areas of the world. As a result, rabid dogs are sometimes considered to be uninfected while anti-rabies treatment is unnecessarily given to persons bitten by animals having other diseases. The saliva of rabid dog contains the rabies virus. Rabies is also caused by cats, monkeys, sheep and goats. The causative agent is found in domestic and wild animals and is transmitted to other animals and humans through close contact with their saliva scratches, licking on broken skin and mucous membrane. The causative agent is a RNA virus, a lyssa virus type I belonging to the family Rhabdoviridae. In India , the disease for the rabies control current policy is to ensure post exposure prophylaxis (PEP) with modern cell culture vaccine to the victim of animal bite . Our main objective is to study about the knowledge regarding animal bites and its management among adults in urban pallavaram (tamilnadu- india). In the study, it showed 8 (27%) of them had moderate knowledge, 22(73%) had inadequate knowledge.